2014
DOI: 10.14423/smj.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Orthopedics Observation Unit as an Alternative to Admission

Abstract: An OOU prevented 138 of 199 (69%) patients from being admitted to a hospital. There were no significant predictors of which patients would require admission. Pain was not a predictor of need for admission. The lack of significant predictors is important in suggesting that without the ability to predict which patients require admission, a system using an OOU can reduce admissions by more than two-thirds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The rate of culture-confirmed MRSA infection was reported by Ernst et al 7 (16 patients, 11.8%) and Schrock et al 10 (64 patients, 35.8%). A history of MRSA infection was reported by Lane et al 9 (50 patients, 5.9%).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The rate of culture-confirmed MRSA infection was reported by Ernst et al 7 (16 patients, 11.8%) and Schrock et al 10 (64 patients, 35.8%). A history of MRSA infection was reported by Lane et al 9 (50 patients, 5.9%).…”
Section: Resultsmentioning
confidence: 71%
“…Both Lane et al 9 and Ernst et al 7 found univariate significance in MRSA exposure and MRSA-positive culture, respectively.…”
Section: Resultsmentioning
confidence: 95%